2015
DOI: 10.1016/j.midw.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study to explore women and clinician׳s response to pain associated with suturing second degree perineal tears and episiotomies [PRAISE]

Abstract: This is a repository copy of A mixed methods study to explore women and clinician ‫׳‬s response to pain associated with suturing second degree perineal tears and episiotomies [PRAISE]. (2015) A mixed methods study to explore women and clinician‫׳‬s response to pain associated with suturing second degree perineal tears and episiotomies [PRAISE]. Midwifery, 31 (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
0
8
0
1
Order By: Relevance
“…Some described being able to recall facial expressions and negative interactions years after the event (Priddis, Schmied, & Dahlen, ; Priddis, Schmied, Kettle, et al., ; Salmon, ), whereas others described how their memories led to their avoidance of intimacy up to 5 years after the event (O'Reilly, Peters, Beale, & Jackson, ). Acknowledging that the suturing procedure can be a painful and traumatic experience for women, a mixed methods study found that women preferred a discursive (and therefore inclusive) communication style during the procedure and described the importance of compassion and communication (Briscoe, Lavender, O'Brien, Campbell, & McGowan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some described being able to recall facial expressions and negative interactions years after the event (Priddis, Schmied, & Dahlen, ; Priddis, Schmied, Kettle, et al., ; Salmon, ), whereas others described how their memories led to their avoidance of intimacy up to 5 years after the event (O'Reilly, Peters, Beale, & Jackson, ). Acknowledging that the suturing procedure can be a painful and traumatic experience for women, a mixed methods study found that women preferred a discursive (and therefore inclusive) communication style during the procedure and described the importance of compassion and communication (Briscoe, Lavender, O'Brien, Campbell, & McGowan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Midwives’ experience was also found to be a protective factor against minor perineal trauma. Although much less attention is given to mild perineal tears, they are much more prevalent than severe tears, and may be associated with significant pain and psychological distress at the time of suturing . Moreover, the majority of women experience some short‐term discomfort or pain after perineal repair, and up to 17.8% of women will have sustained perineal pain 6 months after delivery .…”
Section: Discussionmentioning
confidence: 99%
“…A UK‐based Delphi study found that infection was women's primary concern in the first few weeks after experiencing second‐degree perineal trauma, but women's experiences of infection have rarely been studied. A literature search undertaken for this study in July 2015 exploring women's experiences of first‐ and second‐degree perineal trauma identified only two interviews across six studies with women who experienced a perineal wound infection …”
Section: Introductionmentioning
confidence: 99%
“…A literature search undertaken for this study in July 2015 exploring women's experiences of first-and second-degree perineal trauma identified only two interviews across six studies with women who experienced a perineal wound infection. [19][20][21][22][23][24] Estimates for infection rates in second-degree tears range from 2% to 11% 1,25,26 but defining and identifying clinically relevant infection is challenging. 14,15,25 Estimates for wound breakdown in sutured tears are 0.1%-2%.…”
mentioning
confidence: 99%